Pengaruh Pendapatan Orang Tua Dan Disiplin Belajar Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Iis Halimatusadiah (Herodotus: Jurnal Pendidikan IPS, 2018)
Abstract: This study aims to determine the effect of parental income and learning discipline on social science learning achievement. The research used quantitative approach with survey method. The number of samples is 80 people through simple random sampling. Multiple regression analysis technique is used to analyze data by using SPSS Ver application. 22 for Window. The result of research proves There is significant influence of parent income and discipline learn to social science learning achievement in SMPN Kabupaten Lebak. There is a significant influence of parental income on Social Science learning achievement in SMPN Kabupaten Lebak. There is a significant influence on the learning discipline of learning achievement of Social Sciences at SMPN Kabupaten Lebak.